Meningkatkan Kemampuan Membaca Al-Qur’an melalui Pembelajaran Makhorijul Huruf dengan Metode Game “Tebak Huruf Hijaiyah” - Wa Ode Rizka Fauzia Ali; Iin Septianingsih; Nurhayani Nurhayani; Febi Febi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity aims to improve children's Quran reading skills through learning the hijaiyah alphabet using the "Guess the Hijaiyah Letters" game method. The problem faced by the partners was students' low ability to recognize the hijaiyah letters and their inaccurate pronunciation of the letters according to the hijaiyah alphabet. Furthermore, the monotonous learning process tends to diminish children's interest in learning. Therefore, an educational game-based learning method was implemented to create an active, enjoyable, and interactive learning environment. The activity was implemented through a participatory approach, involving observation, counseling, demonstrations, educational game practice, and evaluation of participant abilities. The "Guess the Hijaiyah Letters" game was used as a learning medium to help children recognize letter shapes, distinguish hijaiyah letter sounds, and gradually practice accurate pronunciation of the hijaiyah alphabet. The activity targeted early childhood and TPA/TPQ students participating in Quran reading lessons. The results showed an increase in participants' ability to recognize the hijaiyah letters, understand the pronunciation of letters according to the hijaiyah alphabet, and increased enthusiasm and participation during the learning process. Educational game methods have been proven to create a more effective and enjoyable learning environment, making it easier for participants to understand Quranic learning materials. Therefore, the "Guess the Hijaiyah Letters" game method can be an innovative learning alternative for improving children's Quranic reading skills.